2021
DOI: 10.1108/ir-09-2021-0193
|View full text |Cite
|
Sign up to set email alerts
|

Constant force control for aluminum wheel hub grinding based on ESO + backstepping

Abstract: Purpose This paper aims to present a control method to realize the constant force grinding of automobile wheel hub. Design/methodology/approach A constant force control strategy combined by extended state observer (ESO) and backstepping control is proposed. ESO is used to estimate the total disturbance to improve the anti-interference and stability of the system and Backstepping control is used to improve the response speed of the system. Findings The simulation and grinding experimental results show that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Xu et al reported a hybrid active/passive force-control strategy [9] and hybrid force/position anti-disturbance control strategy [10] for grinding marks suppression in robotic belt grinding of turbine blade. Dai et al proposed a constant force control strategy combined by extended state observer and backstepping control [11]. Kuma and Rani developed a neural network-based hybrid force/position control [12].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al reported a hybrid active/passive force-control strategy [9] and hybrid force/position anti-disturbance control strategy [10] for grinding marks suppression in robotic belt grinding of turbine blade. Dai et al proposed a constant force control strategy combined by extended state observer and backstepping control [11]. Kuma and Rani developed a neural network-based hybrid force/position control [12].…”
Section: Introductionmentioning
confidence: 99%
“…Burghardt et al (2016) introduced dual robots to implement robotic automation of the turbo-propeller engine blade grinding process. Workpiece calibration and force control in robotic polishing systems have also received considerable attention (Dai et al , 2022; Dai et al , 2021; Mu et al , 2022). A typical robotic polishing system mainly comprises an industrial robot, a machining spindle, a polishing tool, measuring equipment and a control system.…”
Section: Introductionmentioning
confidence: 99%